Magnetic Microparticle Aggregation For Viscosity Determination By Magnetic Resonance - Hong, Rui (2008)
Micron-sized magnetic particles were induced to aggregate when placed in homogeneous magnetic fields, like those of magnetic resonance (MR) imagers and relaxometers, and then spontaneously returned to their dispersed state when removed from the field. Associated with the aggregation and dispersion of the magnetic particles were time dependent increases and decreases in the spin-spin relaxation time (T(2)) of the water. Magnetic nanoparticles, with far smaller magnetic moments per particle, did not undergo magnetically induced aggregation, and exhibited time independent values of T(2). The rate of T(2) change associated with magnetic micro-particle aggregation was used to determine the viscosity of liquid samples, providing a method that can be of particular advantage for determining the viscosity of small volumes of potentially biohazardous samples of blood or blood plasma.